2021
DOI: 10.18332/ejm/131864
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices: Risk perceptions of COVID-19 and satisfaction with preventive measures at workplace among maternity care providers in Pakistan

Abstract: INTRODUCTION While all healthcare services across the globe deferred non-urgent surgeries, labor wards provided maternity care during the pandemic continuously. This study assesses the knowledge and practices of obstetricians and midwives about personal protective equipment (PPE), their risk perception of COVID-19 and satisfaction with the preventive measures adopted at their workplace. METHODS A questionnaire, designed according to the World Health Organization’s advic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
2
4
2
Order By: Relevance
“…These results show a similar satisfaction score for the Gaza Strip and the West Bank, while the level of satisfaction was less in East Jerusalem. This is somewhat in line with the findings of another study by Izhar et al (2020), which found that only 19.5% were satisfied with the social distancing measures in Pakistan ( 23 ). Less than one-third (31%) were satisfied with the PPE available to them.…”
Section: Discussionsupporting
confidence: 91%
“…These results show a similar satisfaction score for the Gaza Strip and the West Bank, while the level of satisfaction was less in East Jerusalem. This is somewhat in line with the findings of another study by Izhar et al (2020), which found that only 19.5% were satisfied with the social distancing measures in Pakistan ( 23 ). Less than one-third (31%) were satisfied with the PPE available to them.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found a high frequency of usage of PPE among midwives as 73.9% always use PPE and 20.5% often use it. This is in consonance with the finding of Izhar et al (2021) among midwives and obstetricians in Pakistan where 78.8% of the respondents had good practices regarding usage of PPE. Given the delicate nature of midwifery care, PPE should be used by midwives always and not sometimes as reported by 64 midwives and rarely as reported by 18 midwives in this study.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, 54.4% of the midwives had adequate knowledge during the first surge of COVID-19. Surprisingly, this level of knowledge in the present study was significantly lower than 89.5%, 88%, 85, and 70% of the level of knowledge among health care providers including midwives that were reported ( Kasahun et al, 2020 ) in China, Northern Ethiopia, Pakistan, and the Amhara region in Ethiopia, respectively ( Asemahagn, 2020 ; Izhar et al, 2021 ; Shi et al, 2020a ; Wuneh et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 88%